PENERAPAN MODEL ALTMAN Z-SCORE UNTUK ANALISIS KEBANGKRUTAN PERUSAHAAN MENGGUNAKAN (SUB SEKTOR PERUSAHAAN MAKANAN DAN MINUMAN TERDAFTAR DI BURSA EFEK INDONESIA) - Fatmawati Isnain; Yusri Kusumayuda; Dedi Darwis (Universitas Teknokrat Indonesia, 2022)
The company was founded with the aim of maximizing profits and maximizing the welfare of stakeholders. The food nd beverage industry plays an important and influential role in Indonesia’s economic growth. Along with the development of the times and the world economy, competition in the business world has become very tight. Not a few companies experience financial difficulties because management is difficult to analyze the company’s financial condition. The Altman Z-Score method can be used as an early warning system to identity early symptoms of bankruptcy so tha company management can be improved. This is what underlies the making of this bankruptcy analysis system so that management can find out the company’s financial condition is in a healthy condition, gray area, or bankrupt. The system development uses the extrame programming method, and uses UML as a tool to analyze the system to be created. The web-based implementation uses the Codeigniter framework, Sublime as a text editor, and MySQL as a database management system. The test results from from this design process can be concluded that the web-bases system of Corporate Bankruptcy Anaysis Using the Atman Z-Score Model in Food and Beverage Companies Listed on the Indonesia Stock Exchange can be used to analyze the financial condition of companies in the healthy, greyarea, or bankrupt categories.